Laryngopharyngeal Reflux (LPR) Correlation to Middle Ear Disorders - Murdiyo, Mohammad Dwijo; Kurniadi, Melody Audria (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Laryngopharyngeal reflux (LPR) is a condition where the reflux of gastric contents reaches the laryngopharynx. Several studies have learned that LPR can cause disturbances in the organs around the larynx pharynx and one of the organs affected is the ear. LPR complications in the middle ear can reduce the quality of life of sufferers. Appropriate diagnostic methods are needed to provide appropriate therapy for this complication. To analyze the relationship between Laryngopharyngeal Reflux (LPR) and middle ear disorders. This study was an analytic observational study using a purposive sampling approach where the assessment of correlation tests between variables was tested with SPSS. Results: Demographic data of LPR patients are dominated by female gender (56%) with an age range of 19 - 59 years (80%). The maximum Reflux Symptom Index (RSI) score in LPR patients is 33 and the maximum Reflux Finding Score (RFS) score in LPR patients is 25. An abnormal Tympanogram Width (Tw) picture was found in 64% of LPR patients. Abnormal compliance picture was found in 36% of patients with LPR and abnormal middle ear pressure picture occurred in 12% of patients with LPR. Abnormal middle ear disorders were found in 88% of patients with LPR. Correlation test assessment between RSI score and Tw parameter and correlation between RFS score and middle ear pressure. There was a positive correlation between LPR and middle ear disorders. There is a positive correlation between LPR and middle ear disorders.